Perceptions of the Pakistani editors for open access journal publishing: a developing country’s perspective - Raza, Muhammad; Rafiq, Muhammad; Soroya, Saira (Information Development, 2025)
Objectives This study has been designed to determine Pakistani editors’ perceptions regarding the Open Access (OA) publishing practices of the Higher Education Commission (HEC)-recognized journals in Pakistan, and to assess their best OA publishing models. Methodology A structured questionnaire-based survey method of quantitative research approach was adopted to achieve the study’s objectives by collecting data from the editors of all 329 HEC-recognized journals in Pakistan. Findings This study exposed that public and teaching institutes are leading in OA journal publishing in Pakistan as compared to private and research institutes. Diamond OA, and Gold OA publishing models are popular among the respondents; however, respondents are not convinced to follow any specific OA publishing model due to their different choices. A large majority (92%) of the journals belong to the Y category (the lowest) of journals. A large majority (72%) of the journals in Pakistan is adopting the Open Journal System (OJS), and parent institutions installed web browsers. CC-BY-NC and CC-BY licenses are their favorite licenses. Significance The present study is the first comprehensive study on editors’ perceptions for OA journal publishing and is an effort to fill this gap to invigorate the scholarly literature. This study may enable the journals, editors, and publishers to follow the best OA journal publishing practices of the Pakistani journals for global OA usage of scholarly journals. The results have practical and theoretical ramifications for academic and research institutions, federal and provincial higher education commissioners, policy organizations, and parent institutions of journals.
Keywords: Computer science; Developing country; Economic growth; Economics; Library science; MEDLINE; Media studies; Open access journal; Open access publishing; Perception; Perspective (graphical); Political science; Psychology; Public relations; Publishing; Scopus; Sociology; dept.ils; peer-reviewed

Perceived awareness, benefits, and strategies of Pakistani editors regarding open-access journal publishing - Raza, Muhammad Zahid; Rafiq, Muhammad; Soroya, Saira Hanif (Global Knowledge, Memory and Communication, 2025)
This study aims to discover the perceived awareness, benefits and suitable strategies of the Pakistani editors of Higher Education Commission (HEC)-recognized scholarly journals regarding open-access (OA) journal publishing in Pakistan.,A structured questionnaire-based survey method of quantitative research approach was adopted to achieve the study’s objectives by collecting data from the editors of 329 HEC-recognized journals in Pakistan.,The awareness level of the respondents of the Pakistani journals is low regarding the OA concepts, resources and initiatives. The respondents of OA journals have better awareness levels than the respondents of non-OA journals. All the respondents of journals are convinced and have the view that OA journals have wider benefits for the academic community, and they need to flourish. A majority of the respondents are of the view that HEC should sponsor financial resources and technical training for OA journal publishing. The respondents of OA journals are more in favor of supporting OA journal publishing than the respondents of non-OA journals.,This study covered the lists of HEC-recognized journals of 2019. More studies may be conducted based on updated lists of HEC-recognized journals by using different research paradigms such as qualitative or pragmatic research approaches.,To the best of the authors’ knowledge, this study is the first comprehensive study on this phenomenon and is an effort to fill this gap and invigorate the scholarly literature. It may attract the attention of the policymakers, funding bodies, parent institutions of the journals and the HEC to cope with the low awareness level of the Pakistani editors regarding the OA concepts, resources and initiatives; and suitable strategies required to uplift the OA journal publishing paradigm in Pakistan.
Keywords: dept.ils; peer-reviewed

Mental Health Needs of Families of Patients in Intensive Care Units and the Role of Mobile Health: Survey Study - Faiola, Anthony; Soroya, Saira; Hao, Zhonglin; Munker, Reinhold (JMIR Formative Research, 2025)
BACKGROUND: The experiences of patients with COVID-19 and their families manifested the most devastating effects of family separation since the 1918 Spanish influenza pandemic and, with it, a call for solutions to patient isolation and its effect on family mental health. OBJECTIVE: This study examined the recent experiences of families of critical care (intensive care unit; ICU) patients related to anxiety and depression (AD), satisfaction with clinician-family communication, and counseling from mental health and social services. This study explored correlations between these factors and family interest in mobile health (mHealth) designed to improve information flow and communication from patient bedside to remote families. METHODS: Using a 36-question quantitative survey, we collected 97 responses over 6 months. We selected participants by using a convenience sampling strategy. To analyze data, we applied descriptive and inferential statistics. Participants represented a spectrum of ages, relationships to patients, and races (n=78, 80% White; n=17, 18% Black; n=2, 2% other races). Approximately 17% (n=16) of the patients were admitted for cancer, 13% (n=13) were admitted for COVID-19, and 21% (n=20) were admitted for other conditions. RESULTS: The mean score for remote families' satisfaction with patient health updates from the bedside and mental health services was 2.94 (SD 1.31), whereas that for phone communication was lower on average. The mean scores of family AD levels were elevated, and levels were higher among family members during the ICU stay than after discharge. These findings confirmed evidence of a negative correlation between transportation difficulties and satisfaction with the frequency of information provided (r=-0.284; P=.005), suggesting that, with the increase in transportation challenges, families become less satisfied with the frequency of patient health information. Family members expressed strong interest in using mHealth information and communication services (mean 8.34, SD 1.98) and having easy access to social workers to manage AD (mean 8.29, SD 2.03). Families experiencing higher levels of anxiety during patients' ICU stays had significantly greater interest in the use of an mHealth app that would provide direct access to social workers (r=0.326; P<.001), in using an mHealth videoconferencing app (r=0.319; P=.002), and in overall mHealth app use (r=0.322; P<.001). CONCLUSIONS: Family members experienced high levels of AD during patient ICU admission, as well as after discharge even though their mental health challenges were reduced. Families were highly dissatisfied with the frequency of health updates, with lower satisfaction reported among those who faced difficulties arranging transportation or lived further from the hospital. Modest but statistically significant correlations were observed between family members' reported mental health status during ICU stays and an interest in an mHealth app that could provide access to real-time bedside information, facilitate communication with bedside nurses, and support connections with social workers.
Keywords: Affect (linguistics); COVID-19; Depression (economics); Health care; ICU; Mental health; Mental illness; Receipt; communication; dept.ils; digital tools; eHealth; health equity; health technology; intensive care unit; mental health; mobile health

The influence of responsible leadership on organizational commitment: the mediating role of trust in leaders in the higher education sector - Afzal, Muhammad; Soroya, Saira; Chaudhary, Naveed; Niazi, Abdul; Ashiq, Murtaza (RADS Journal of Business Management, 2025)
Background: This study examines the impact of responsible leadership (RL) on organizational commitment by examining the mediating role of trust in the leader, as modeled by the four key dimensions of the leader's role (aggregate of virtues, principles and ethical values, stakeholder involvement, and model of the leader's role) in the context of social identity theory. Methods: We employed a quantitative research design, surveying 300 middle-level employees in grades 11 to 16 from the University of the Punjab, Lahore, Pakistan. Data collection involved a structured questionnaire covering key leadership and trust dimensions. The data analysis utilized SPSS version 22 and ADANCO version 2.2, with structural equation modeling to test hypotheses. Results: Results show that organizational commitment is significantly influenced by stakeholder involvement (0.03 p-value) and ethical principles (0.00 p-value). The aggregate of virtues (0.79 p-value) and leadership role modeling (0.26 p-value) have an insignificant direct impact. However, trust significantly mediates the relationship between organizational commitment and stakeholder involvement (0.01 p-value). Trust’s mediation effect on the link between ethical principles and organizational commitment is minimal (0.04 p-value). Conclusion: This study suggests that implementing RL practices, particularly in stakeholder involvement and ethical leadership, enhances employee commitment. Responsible leadership cultivates a positive corporate image, attracting committed stakeholders. To maximize benefits, organizations should provide senior leaders with behavioral training in RL practices, fostering an environment that boosts employee loyalty. Leadership development programs should include modules on ethical decision-making, stakeholder communication, and trust-building strategies.
Keywords: Context (archaeology); Ethical leadership; Mediation; Organizational commitment; Stakeholder; Stakeholder engagement; Stakeholder theory; Structural equation modeling; dept.ils